Portfolio Based Language Assessment (PBLA) in Language Instruction for Newcomers to Canada (LINC) Programs: Taking Stock of Teachers' Experience - Abdulhamid, Nwara; Fox, Janna (Canadian Journal of Applied Linguistics / Revue canadienne de linguistique appliquée, 2020)
This study examined seven Language Instruction for Newcomers to Canada (LINC) teachers’ accounts of current Portfolio Based Language Assessment (PBLA) practices, elicited through semi-structured interviews, in order to explore washback - the effects of PBLA on teaching and learning. Portfolios are primarily useful as formative assessment tools (i.e., informing teaching and learning) (Fox, 2014; Little, 2007); conversely, when used solely as summative tools (i.e., achievement measures), they can result in portfolio prisons, which undermine teaching and learning (Hargreaves et al., 2002). To investigate the washback effect of PBLA, data were qualitatively analyzed, synthesized, and merged in development of recurring themes (Charmaz, 2006). Findings suggest that PBLA may have had washback on both teaching and learning. However, teachers’ individual classroom situations determined the direction and intensity of reported PBLA washback. The study highlights leverage points (Fox, 2004) where interventions (e.g., additional support, resources) might address negative washback.